The factors that influence learning organization among managers in City Hall of Kuala Lumpur / Farah Hida Sharin - Sharin, Farah Hida (Faculty of Business and Management, 2008)
The knowledge revolution, global competition and growing expectations for performance drive every organization to enhance more efficient and effective learning in management and development of its human capital. Therefore, it is important for the organization to practice learning the theory of the organization in order to create continuous improvement in various scopes of work. This research is about the factors that influence learning organization among managers in City Hall of Kuala Lumpur. Factors of learning organization such as training and education, reward and recognition, information flow and vision and strategy have been identified in order to investigate whether or not these factors have a significant relationship with the dimension of learning organization. The survey was conducted in 24 departments in City Hall of Kuala Lumpur such as the Administration Department; Civil Engineering Department; Culture, Arts, Tourism and Sports Department; Human Resource Management Department; Information Technology and Communication Department and others. The sample size for this study was 100 officers who had a bachelor's degree in different courses study and involved decision making in City Hall of Kuala Lumpur. Data was obtained using two methods which were primary and secondary data. Respondents were required to answer the questionnaires that include the statements regarding the factors that influence learning about organization among managers in City Hall of Kuala Lumpur. Once the necessary data was collected, the data was analyzed and summarized in a readable and easily interpretable form. The Statistical Package for the Social Science (SPSS) version 12.0 was used to summarize the data. The results are in the form of reliability testing, descriptive statistics, ANOVA, t-test and correlation. Based on this research, the result indicates that all factors have a significant relationship between all the elements of learning organization which include continuous learning, inquiry and dialogue, team learning, empowerment, embedded system, system connection and strategic leadership. The conclusion of the study is the outcome of the survey analysis and findings. Based on findings, some recommendations have been suggested in order to help increase learning organization and for future research.